Attack in to The Server Message Block (CVE-2020-0796) Vulnerabilities in Windows 10 using Metasploit Framework - M. Faturrohman; Angelita Salsabila; Zulma Mardiah; Aqwam Rosadi Kardian (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
Advances in information and communication technology encourage the development of operating systems. Windows 10 is one of the most widely used operating systems today. Unfortunately, there are still many who do not know that in the Windows 10 system there are several system vulnerabilities and some bugs. One example is the vulnerability in Server Message Block (SMB) on Windows 10 (CVE-2020-0796). This vulnerability exploits the Buffer Overflow method on one of the Execution Server Message Block (SMB) files. The impact of this attack is that the attacker can perform Remote Control Access on the target device. One of the reasons why this attack can occur is an operating system that has never been updated or uses an old operating system that has lots of bugs. The automatic updating feature is actually very helpful in overcoming this problem. However, there are still many device users who understand the importance of this. This research will explain how the process of attacking the Windows 10 operating system uses the CVE-2020-0796 vulnerability. The hope is that after understanding the readers can know the importance of using the latest version of the operating system and immediately updating the system.